LUPUS VASCULITIS - Butt, Nauman Ismat; Ashfaq, Fahmina; Mehmood, Khalid; Aftab, Sabeen; Anwar, Ali; Saeed, Minhal (Journal of Ayub Medical College Abbottabad, 2023)
We present the case of a 30-year-old woman who presented with 8-month history of intermittent fever, joint pains with morning stiffness, recurrent oral ulcers, photosensitivity, weight loss and hair fall. For the last 2 month she had developed dry cough with progressive shortening of breath. On examination, a cachexic lady with malar hyperpigmentation, alopecia, pallor, nail dystrophy and erythema over hands and feet were noted. There were multiple punched-out skin ulcers of variable size over legs, arms and abdomen usually round in shape with well-defined even wound margins and scant serous discharge. Musculoskeletal examination revealed synovitis of both elbows and few metacarpophalangeal and proximal interphalangeal joints. Chest X-ray and HRCT showed bilateral ground-glass opacification. Anti-Nuclear Antibody (ANA) was positive, 1:320, homogenous nuclear pattern. Anti-Ro antibody was high positive and serum complement (C3, C4) levels were reduced. She was diagnosed as Lupus Vasculitis and started on steroids, mycophenolate mofetil and hydroxycholoroquine.